Patient-Reported Outcomes After Extensive (Ultraradical) Surgery for Ovarian Cancer: Results From a Prospective Longitudinal Feasibility Study. Issue 9 (1st November 2015) - Soo Hoo, San; Marriott, Natalie; Houlton, Aimee; Nevin, James; Balega, Janos; Singh, Kavita; Yap, Jason; Sethuram, Ramya; Elattar, Ahmed; Luesley, David; Kehoe, Sean; Sundar, Sudha
Abstract : Background: Extensive (ultraradical) surgery may facilitate complete cytoreduction in ovarian cancer with potential survival benefit but with greater morbidity. Currently, patient-reported outcomes (PROs) from such surgery are unknown. We conducted the Surgery in Ovarian Cancer Quality of life Evaluation Research study (SOCQER 1), a prospective study investigating the feasibility of collection of serial PROs in patients who had extensive surgery and standard surgery for ovarian cancer. Methods: Ninety-three patients were recruited for 33 months to complete serial PRO assessments using the validated EORTC QLQ-C30 and the ovarian cancer–specific QLQ-OV28 questionnaires preoperatively, at 6 weeks, and at 3, 6, and 9 months postoperatively. Aletti Surgical Complexity Score of 3 or lower was considered standard surgery ; a Surgical Complexity Score of 4 or higher was considered extensive surgery . Prospective data collection was obtained from the hospital electronic database, including patient demographics, American Society of Anaesthesiologists grade, preoperative serum CA125 and albumin levels, chemotherapy regimen, and surgical morbidity. Results: Three cohorts of patients—32 benign, 32 undergoing standard surgery, and 24 undergoing extensive surgery—completed the questionnaires. Median questionnaire completion rate in this study was 64%, demonstrating the feasibility of longitudinal quality of life (QoL) assessment after surgery. Patient-reported outcomes revealed a falling trend in QoL in the short-term (6 weeks-3 months) after surgery, which gradually returned to baseline at 6 to 9 months; this trend was more marked after extensive surgery. Conclusions: This study provides useful insight into the impact of extensive surgery on patients. Further multicenter studies are needed to evaluate the impact of extensive surgery on patient's QoL and survival.